2011
DOI: 10.1097/scs.0b013e318231fca3
|View full text |Cite
|
Sign up to set email alerts
|

Are Facial Injuries Caused by Stumbling Different From Other Kinds of Fall Accidents?

Abstract: The aim of this prospective study was to evaluate and compare the epidemiology and pattern of maxillofacial injuries caused by stumbling and other kinds of falls. We evaluated all patients with facial injuries due to stumbling or falls who presented to Besat Hospital in Hamedan, Iran, during the 2.5-year study period and analyzed the acquired data. Of 2990 patients with facial injuries who were referred to Besat Hospital during the study period, 733 (24.5%) were injured by stumbling, and 246 (8.2%) were injure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
6
11
0
Order By: Relevance
“…Hematoma was the most frequent associated soft tissue lesion in the current study, which is also reported by other authors [2,4,19,20]. Contrary to our results, other authors indicate the highest incidence of laceration [21,22]. The fact that in the current study hematomas are predominant shows that the severity of the injuries included in this study is reduced.…”
Section: Discussionsupporting
confidence: 65%
“…Hematoma was the most frequent associated soft tissue lesion in the current study, which is also reported by other authors [2,4,19,20]. Contrary to our results, other authors indicate the highest incidence of laceration [21,22]. The fact that in the current study hematomas are predominant shows that the severity of the injuries included in this study is reduced.…”
Section: Discussionsupporting
confidence: 65%
“…This high prevalence of fall among children may be because of the fact that children are more involved in activities such as playing, running, jumping both at school, and while running errands. 26 It may also be that their motor coordination is not yet optimal and as such they are a group of people who can stumble and fall easily. Maxillofacial injuries following falls have been hardly reported before in the literature from our geographical region.…”
Section: Discussionmentioning
confidence: 99%
“…In the STSF patients, fractures of the middle third (especially OZM fractures) were predominant, as in the other groups, with the exception of LOCF patients. The injury severity was lower than in the other groups, probably because in this type of fall the patient instinctively tries to stop the fall, thereby minimising the impact with the ground [ 8 , 14 , 31 ]. This explains the threefold greater frequency of orthopaedic “protection” injuries (especially to the upper limbs) in comparison with the LOCF group.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles studied and considered falls alone [ 8-10 ]. Other articles examined falls according to patient age; i.e., falls in the paediatric population [ 11 ] or in old patients [ 12 ], according to height [ 13 ], or according to the cause of the falls, such as slipping and tripping [ 14 ], loss of consciousness [ 15 ], epilepsy [ 16-18 ], and bicycle accidents [ 19-21 ].…”
Section: Introductionmentioning
confidence: 99%